Analyzing the efficacy of comprehensive testing: a comprehensive evaluation - Alolaywi, Yasamiyan; Alkhalaf, Shatha; Almuhilib, Badar (Frontiers in Education, 2024)
This study aimed to examine the variations in comprehensive exam results in the English department at Qassim University in Saudi Arabia across six semesters, focusing on average score, range, and standard deviation, as well as overall student achievements. Additionally, it sought to assess the performance levels of male and female students in comprehensive tests and determine how they differ over the past six semesters. The research design utilized both analytical and descriptive approaches, with quantitative analysis of the data using frequency statistics such as mean, standard deviation, and range. The data consisted of scores from six consecutive exit exams. The findings reveal that male students scored slightly higher on average than female students, with minimal difference (p=.07). Moreover, male scores exhibited more variability and spread, indicating varying performance levels. These results suggest the need for further investigation into the factors that contribute to gender-based differences in test performance. Furthermore, longitudinal studies tracking individual student performance over multiple semesters could offer a more in-depth understanding of academic progress and the efficacy of comprehensive exam practices.